2012
DOI: 10.1007/s10554-012-0051-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thoracic aortic calcification and its relationship to cardiovascular risk factors and coronary calcification in an unselected population-based cohort: the Heinz Nixdorf Recall Study

Abstract: Thoracic aortic calcification (TAC) and coronary artery calcium (CAC) have been proposed for risk assessment of coronary artery and cardiovascular disease events. The aim of this analysis is to assess the prevalence of TAC and to determine its relationship with cardiovascular risk factors and CAC in a general unselected population. TAC was measured from electron beam computed tomography scans and quantified by Agatston-Score in 4,025 participants aged 45-75 years (mean age 59.4 ± 7.8 years, 53% female) from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
3
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 30 publications
1
40
3
3
Order By: Relevance
“…20,21 This stands in contrast to the Heinz-Nixdorf Recall Study, where ATAC was present in 43% of subjects. 22 Nonetheless, due to low ATAC prevalence, the findings of our study do not support widespread imaging of the ascending thoracic aorta. This was reflected in the marginal and non-significant increase in the AUC beyond that provided by both CVD risk factors and CAC when evaluated in the full cohort.…”
Section: Discussioncontrasting
confidence: 77%
“…20,21 This stands in contrast to the Heinz-Nixdorf Recall Study, where ATAC was present in 43% of subjects. 22 Nonetheless, due to low ATAC prevalence, the findings of our study do not support widespread imaging of the ascending thoracic aorta. This was reflected in the marginal and non-significant increase in the AUC beyond that provided by both CVD risk factors and CAC when evaluated in the full cohort.…”
Section: Discussioncontrasting
confidence: 77%
“…However, generally valve atherosclerosis is encountered earlier than coronary atherosclerosis 25. Atherosclerosis is a diffuse process that may affect different vascular beds with considerable overlap between coronary, cerebrovascular and peripheral arterial disease 26. It is possible that due to its early occurrence and the high prevalence of metabolic syndrome, the prevalence of AVC limits its discriminatory predictive power.…”
Section: Discussionmentioning
confidence: 99%
“…reported that the aortic calcium score was associated with BMI, SBP, and pulse pressure. [36] A significant independent association between the total plaque score and MS was observed in males. [37] MS components are related to GD, and BMI and increased age are also related to GD.…”
Section: Discussionmentioning
confidence: 99%